The Coincidence of Ovarian Endometrioma with Paratubal Leydig Cell Nodules: A Case Report and Literature Review - Pei-An Chen; Chiu-Hsuan Cheng; Dah-Ching Ding (Diagnostics)
Background and Clinical Significance: Paratubal Leydig cell nodules are rare incidental findings that present diagnostic challenges. Case Presentation: A 45-year-old female with a history of hypertension and diabetes mellitus presented with fever and chills following an episode of severe dysmenorrhea and menorrhagia. The patient reported heavy menstrual bleeding, persisting for 2–3 years. Physical examination revealed erythema of the perineum and whitish vaginal discharge, with no cervical lesions. Imaging revealed a 15 cm right ovarian cyst. Laboratory investigations showed elevated C-reactive protein (6.37 mg/L) and CA125 (88.82 U/mL) levels, whereas other tumor markers were within normal limits. A pelvic ultrasound revealed a retroverted uterus and a large ovarian mass suggestive of malignancy. The patient underwent a right salpingo-oophorectomy, during which a 15 cm ovarian tumor adherent to the right pelvic sidewall was excised. Histopathological examination revealed an endometriotic cyst with endometrial glandular epithelium positive for estrogen receptor and focal mucinous metaplasia. CD10-positive endometrial stromal cells and paratubal cysts were also observed. Additionally, a small Leydig cell tumor originated from the ovarian hilum was identified and confirmed by positive staining for inhibin, calretinin, and androgen receptors, as well as negative estrogen receptor staining. The postoperative recovery was uneventful, and at the five-week follow-up, the patient’s hormonal levels were normal, and there were no complications. Conclusions: This case highlights the importance of thorough histopathological evaluation in managing ovarian masses and the potential coexistence of benign and rare pathological entities, such as Leydig cell tumors.